Nostalgia for the Empire and the modern image of Spain: inspired by Carrera & Carrera jewelry house collection «Treasures of the Empire» - A. A. Koroleva (Ибероамериканские тетради, 2015)
The article touches upon peculiar for the Spaniards nostalgia for the Spanish imperial past. Information society is characterized by growing influence of the symbolic capital of national culture alongside with importance of international prestige of national values. The main topic is the exploration of the “made in” effect and its influence on modern image of Spain. The scientific novelty of the work lies in the application of semiotic analysis of contemporary jewelry art visualizing the Golden Age of Spanish culture heritage, in order to express the importance of symbolic interpretation of the archetypal image in technologies of national branding.